Because I Don't Have Wings : Stories of Mexican Immigrant Life - Garrison, Philip (Book collections on Project MUSE., 2006)
"For Mexican workers, the agricultural valleys of the inland Northwest are a long way from home. But there they have established communities, settlements recent enough that it feels like these newly arrived immigrant mexicanos are pioneers, still getting used to the Anglos and to each other." "Written with irony but bursting with compassion, Because I Don't Have Wings features vivid characters, telling anecdotes, and poignant reflections on life, unfolding an immigrant's world strikingly different from the one we usually read about. Adaptation, persistence, and survival, we learn, are traits that mexicano culture values. We also learn that, over time, mexicano immigrants don't merely adapt to the culture of el norte, they transform it."--Jacket.